Analisis Strategi Pemasaran Rumah Jahit Hafsah Menggunakan Pendekatan Bauran Pemasaran 4P - Fatimah; Jumai Latte (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: Micro, Small, and Medium Enterprises (MSMEs), locally known as UMKM, play a strategic role in Indonesia’s economy, particularly in rural areas far from major trade centers. One of the service sectors experiencing continuous growth is tailoring, which typically involves personalized services and builds strong, trust-based relationships with customers. Home-based tailoring businesses offer economic opportunities, especially for women, enabling them to earn income while managing household responsibilities. This study focuses on Rumah Jahit Hafsah, a home-based tailoring business in Desa Hakurung, Kecamatan Daha Utara, which has demonstrated significant growth since its establishment in 2018. The research analyzes the marketing strategies employed by Rumah Jahit Hafsah through the 4Ps marketing mix framework: Product, Price, Place, and Promotion. Using a qualitative descriptive approach, data were collected through field observations and unstructured interviews with the business owner and customers. The findings reveal that Rumah Jahit Hafsah effectively applies marketing strategies tailored to customer needs and local market conditions, allowing the business to remain competitive despite seasonal fluctuations and competition from similar enterprises. This study contributes to the literature on marketing strategies for micro enterprises and offers practical insights for tailoring businesses aiming for sustainable growth through targeted marketing approaches